High altitude pulmonary edema - Bärtsch, Peter (Respiration, 1997)
Altitude, speed and mode of ascent and, above all, individual susceptibility are the most important determinants for the occurrence of high-altitude pulmonary edema (HAPE). This illness usually occurs only 2-5 days after acute exposure to altitudes above 2,500-3,000 m. Chest radiographs and CT scans show a patchy predominantly peripheral distribution of edema. Wedge pressure is normal at rest, and there is an excessive rise in pulmonary artery pressure (Ppa) which precedes edema formation. Bronchoalveolar lavage in patients with advanced HAPE shows evidence of inflammatory response with increased capillary permeability. There are, however, no prospective data indicating whether the inflammatory response is a primary cause of HAPE or a consequence of edema formation. Excessive rise in Ppa appears to be a crucial pathophysiologic factor for HAPE. Recent observations of high Ppa in HAPE-susceptible sujects who did not develop pulmonary edema after rapid ascent to high altitude suggest either that Ppa does not necessarily reflect capillary pressure in these individuals or else that additional factors, such as an inflammatory response and/or a decreased fluid clearance from the lung, are necessary for the development of pulmonary edema. The treatment of choice is immediate descent. When this is impossible and supplemental oxygen is not available, treatment with nifedipine is recommended until descent is possible.
Elektronische Reproduktion der Druck-Ausgabe 21. Januar 2009
Gesehen am 29.01.2024